PESAN KERUKUNAN CERITA LISAN MASYARAKAT TENGGER DESA NGADAS KABUPATEN MALANG (Harmonious Messages On The Folklore Of Tengger Community In Ngadas Village, Malang Indonesia) - Joko Tri Haryanto (Balai Penelitian dan Pengembangan Agama Semarang, 2016)
Tengger community in Ngadas village Malang district has lived in harmony although those people follow three different religions as follows; Islam, Buddha and Hinduism. The harmonious values in that village have been transmitted from generation to next one by preserved folklore. This article concerns on the messages contained in the story of Roro Anteng-Joko Seger and the story of Setya-Setuhu- Ngadas Malang village version. This study uses hermeneutic approach. Findings of this research show that those stories contain valuable harmonious messages. The story of Roro AntengJoko Seger implies that a person should give the other’s good deed back to them. Furthermore, this story, then, created Kasada Ceremony and “gentenan” tradition among Tengger community. Meanwhile, the story of Setya-Setuhu is the origin of Karo tradition, a ritual to commemorate the death of two figures named Setya-Setuhu. This story depicts moral values for people in order to avoid conflict through respecting diversity and not claiming as the only one who is right in the society.